Dropout phenomenon in a higher education institution in the North of Portugal, and the reasons behind it - Lopes, Marina (2022)
School dropout is a problem that directly affects higher education students, this education system and, consequently, society, since, in the perspective of an economy increasingly supported by knowledge and innovation, higher academic qualifications are given relevance. During the transition to higher education there are vicissitudes that, associated with the individual characteristics of each student, may directly affect the integration, adaptation, permanence, and success of students in the course and/or institution where they were placed. The analysis of the bibliography out points to different reasons that may lead higher education students to abandon their studies. The present research aimed at understanding the extent of the dropout phenomenon in a higher education institution in the North of Portugal, and the reasons behind it. It had as objectives: 1) to survey the data concerning school drop-outs in this institution, through the analysis of the students' cancelled enrolments; 2) to analyze the reasons for dropping out stated by the students who cancel the enrolments. This research involved 612 students, being 50.16% (n=307) female and 49.84% (n=305) male, aged between 18 and 71 years (at the time of annulment) and an average age of 25 years. To achieve the objectives, we performed a documentary analysis of the official data on the annulments of enrollment of students in three consecutive years, even before the Covid-19 Pandemic. In the survey we identified the number of annulments of enrollment in the period under study, as well as the reasons given by students when they canceled their enrollment. This resulted in the construction of a database for statistical purposes in a Microsoft Excel sheet that was available for later consultation and updating. In the process of building the database, a documentary analysis was made of the justifications presented by the students when they applied for cancellation of enrollment, and these were subjected to a content analysis process. The analysis and discussion of the results allowed us to conclude that: (i) in the triennium studied 5.88% (n=612) students left the institution; (ii) the first curricular year was the year in which the highest percentage of annulments was observed; (iii) the main reasons for the annulment were personal, professional, economic difficulties and academic reasons. In addition to the reasons mentioned by students for dropping out of this higher education institution, and similarly to what is mentioned in the literature, this research allowed us to understand that the integration and adaptation of students to institutions and to the academic context are also very important and should be taken into account when the subject of concern and study is dropout. It was also perceived that issues such as academic difficulties, related to the act of studying itself, are little explored and worked on, so they may end up remaining and may imply that students who cannot overcome them end up failing and/or dropping out of their studies. It is important to emphasize the relevance of the data obtained, which, being from years prior to the Covid-19 Pandemic, may constitute a term of "comparison" with data collected during and after this same Pandemic.